Formulation Development of Carvedilol Phosphate and Lisinopril Hydrochloride Bilayer Tablet using QbD - Kulkarni, Kapil; Deokar, Gitanjali (International Journal of Pharmaceutical Investigation, 2026)
Introduction Lisinopril HCl (LH) and Carvedilol Phosphate (CP) combination bilayer tablet to be developed for the treatment of hypertension. Objectives To develop carvedilol phosphate and lisinopril hydrochloride bilayer tablet using QbD. Materials and Methods Bilayer tablet technology is used for the development of the combination of LH and CP to achieve two different release profiles of each drug. LH containing layer released the drug at a much faster rate due to faster disintegration time and CP containing layer swells and releases the drug content for a longer period by forming the swellable matrix. The central composite design is used for the development and optimization of the formulation of bilayer tablets. Critical responses like disintegration time and dissolution for the LH layer and dissolution at 2 hr, 16 hr, and 24 hr for the CP layer were evaluated against factors like Maize starch, Crospovidone XL for the LH layer, and concentration of HPMC K 100M and MA Polymer for CP layer. The wet granulation method was used for the preparation of granules and further processing of bilayer tablets. Results Critical responses were evaluated by response surface methodology by design expert software to verify the best-fit model for the development and optimization bilayer tablet. Responses obtained for the LH layer show that the concentration of maize starch and crospovidone XL and for the CP layer concentration of HPMC K100M and MA Polymer need to be optimized to achieve desired responses for both layers. The model selected was found to be significant as per ANOVA tables. Conclusion The evaluation of results of the LH layer found that the concentration of maize starch (3%) and crospovidone XL (10%) and the CP Layer found that concentration of HPMC K100M (34%) and MA polymer (17%) were found best composition.
Keywords: Bilayer tablets; Hypertension; Central Composite Design; ANOVA; Response surface methodology